2014
DOI: 10.4238/2014.november.28.2
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis demonstrates no association between XRCC1 Arg399Gln polymorphism and bladder cancer risk

Abstract: ABSTRACT. We examined whether the X-ray repair crosscomplementing group 1 (XRCC1) Arg399Gln polymorphism is a risk factor for bladder cancer by conducting a meta-analysis. We searched the Pubmed and Embase databases for study retrieval. This meta-analysis examined 16 case-control studies, including 892 prostate cancer cases and 1020 healthy controls. Meta-analysis results based on these studies showed no significant association between the XRCC1 Arg399Gln polymorphism and bladder cancer risk in comparisons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…In X-ray repair cross-complementing protein 1 (XRCC1), rs1799782 and rs25489 are widely associated with an increased risk for BC, especially in Asian and Indian populations [146][147][148][149][150][151][152]. Rs915927 in the same gene increases tumor susceptibility in the Italian population [153] while rs25487 gave contradictory results in different studies [147][148][149][154][155][156][157][158][159]. Rs3218373, rs3218536, and rs6464268 in XRCC2 present a protective effect towards BC in the Italian population [160].…”
Section: Dna Repairmentioning
confidence: 99%
“…In X-ray repair cross-complementing protein 1 (XRCC1), rs1799782 and rs25489 are widely associated with an increased risk for BC, especially in Asian and Indian populations [146][147][148][149][150][151][152]. Rs915927 in the same gene increases tumor susceptibility in the Italian population [153] while rs25487 gave contradictory results in different studies [147][148][149][154][155][156][157][158][159]. Rs3218373, rs3218536, and rs6464268 in XRCC2 present a protective effect towards BC in the Italian population [160].…”
Section: Dna Repairmentioning
confidence: 99%
“…1 4 XRCC genes are involved in base excision repair (BER) and single-strand break in damaged DNA in human genome. 1 5 Molecular epidemiological studies have shown that XRCC genes are significantly associated with lung cancer, 6 9 oral cancer, 10 bladder cancer, 11 13 ovarian cancer, 14 , 15 esophageal cancer, 16 and gastric cancer. 17 23 Moreover, studies have revealed that XRCC gene polymorphism is highly variable in different ethnic populations.…”
Section: Introductionmentioning
confidence: 99%
“…В ряді робіт показана асоціація носійства поліморфних алелей гену XRCC1 з ризиком розвитку ряду злоякісних новоутворень (рак молочної залози, рак шлунка, колоректальний рак, рак легень) [21][22][23][24]. Поряд з тим, існують роботи, в яких не виявлено подібних асоціацій [25,26]. Показано, що за умов дії іонізуючої радіації у гомозиготних носіїв поліморфного алелю XRCC1 Gln399Gln швидкість репарації пошкоджень ДНК менша, ніж у гомозигот за домінантною алеллю [27].…”
unclassified